Oceanic Eddy Characteristics and Generation Mechanisms in the Kuroshio Extension Region. Issue 11 (26th November 2018) - Ji, Jinlin; Dong, Changming; Zhang, Biao; Liu, Yu; Zou, Bin; King, Gregory P.; Xu, Guangjun; Chen, Dake
Abstract: The Kuroshio Extension region is well known for its strong eddy activity. In this paper, using satellite altimetry‐measured sea surface height anomaly data from 1993 to 2012 in an extended Kuroshio Extension region (140–180°E, 25–45°N), we analyze eddy characteristics: eddy size, polarity, lifetime, intensity, trajectory, and spatial and temporal distributions. Using temperature and salinity vertical profiles measured by Argo floats, we examine the eddy impact on vertical stratification. During the 20‐year period, 7, 574 eddies are identified (based on following complete eddy trajectories) with a lifetime equal to or longer than 4 weeks. The numbers of cyclonic and anticyclonic eddies are found to be approximately the same. The distribution of eddy sizes peaks at a radius of about 40 km. The radius at the peak is at the same order as the first baroclinic deformation radius or the horizontal shear scale of the Kuroshio flow. The normalized eddy statistical characteristics show that eddies have different characteristics at different stages of their lifetimes. Among eddies with lifetimes longer than 50 weeks, more anticyclonic (cyclonic) eddies are found north (south) of 35°N. In contrast, among eddies with lifetimes shorter than 20 weeks, more cyclonic (anticyclonic) eddies are found north (south) of 35°N. The asymmetric distribution of eddies suggests two different eddy generation mechanisms: (1) the development of meanders in the Kuroshio path leading to the pinch off of eddies with longer lifetime (larger size) and (2) horizontal shear instability (barotropic instability) leading to eddies of shorter life (smaller size). We further apply an eddy‐resolved numerical product to quantitatively investigate the eddy generation mechanisms. Plain Language Summary: We analyze eddy characteristics with 20‐year satellite data and examine the eddy impact on vertical stratification. Besides, through the statistic result, we propose two eddy generation mechanisms: flow horizontal shear‐induced eddy generation and the meander of flow path leading to the eddy generation. And then, we further apply an eddy‐resolved numerical product to quantitatively investigate the eddy generation mechanisms. Key Points: We analyze eddy characteristics We examine the eddy impact on vertical stratification We discuss two eddy generation mechanisms and apply an eddy‐resolved numerical product to quantitatively analyze eddy generation mechanisms